1792 N.C. Sess. Laws 33 - (:unkn) unknown (My University, 1792)
The minimum age remained 18, while the maximum dropped to 45. The mandatory arms paralleled the federal statute. Each infantryman was required to "provide himself with a good musket or firelock, a sufficient bayonet and belt, two spare flints, a knapsack, a pouch with a box therein to contain not less than 24 cartridges suited to the bore of his musket or firelock, each cartridge to contain a proper quantity of powder and ball ; or with a good rifle, knapsack, shot-pouch and powder-horn, 20 balls suited to the bore of his rifle, and a quarter of a pound of powder."
Keywords: MILITIAS; REQUIRED POSSESSION